2021
DOI: 10.1016/j.jclepro.2021.129200
|View full text |Cite
|
Sign up to set email alerts
|

The wicked problem of waste management: An attention-based analysis of stakeholder behaviours

Abstract: Surging amounts of waste are reported globally and especially in lower-income countries, with negative consequences for health and the environment. Increasing concern has been raised for the limited progress achieved in practice by diverse sets of policies and programmes. Waste management is a wicked problem characterised by multilayered interdependencies, complex social dynamics and webs of stakeholders. Interactions among these generate unpredictable outcomes that can be missed by decision makers through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 46 publications
1
21
0
1
Order By: Relevance
“…Both Govender and Reddy 42 and Salvia et al 43 confirm the constructions of similar value systems and personality traits of those who litter. [44][45][46] Chaudhary et al 6 identified five stages of litter research in developed countries.…”
Section: Theme 1: Value Systems and Personality Traitsmentioning
confidence: 68%
“…Both Govender and Reddy 42 and Salvia et al 43 confirm the constructions of similar value systems and personality traits of those who litter. [44][45][46] Chaudhary et al 6 identified five stages of litter research in developed countries.…”
Section: Theme 1: Value Systems and Personality Traitsmentioning
confidence: 68%
“…According to G. Salvia et al the problem of waste management is one of the most important in modern world, as the absence of the system approach to solving the problems in this area causes negative consequences for environment as well as for health of the local communities [8]. As for Ukraine, according to the research of I. Kolodiichuk and V. Kolodiichuk major part of Ukraine's regions is characterized by the imbalance in the amounts of waste generated and capabilities for their disposal.…”
Section: Results Of the Researchmentioning
confidence: 99%
“…An important role in the set of issues of environmental management and management of interaction with environment is played by waste management. In particular, a group of authors led by G. Salvia [8] consider the peculiarities of stakeholders interaction in the waste management process on the example of Kenyan city Kisumu. The authors apply the attention-based view from organization theory to define the key problems in the relevant sphere and ways of their solving.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The initial focus is on community management of solid waste, a pressing issue for which an analytical investigation by CUSSH showed how the actors involved hold different, often contrasting views about the sources of the underpinning causes and possible solutions ( Salvia et al , 2021 ). Public engagement may contribute towards the alignment or at least the integration of divergent stakeholder views, in order to limit chances of unintended consequences from policy implementations.…”
Section: Public Engagementmentioning
confidence: 99%